2021
DOI: 10.1007/s00520-021-06629-4
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in telehealth use: How should the supportive care community respond?

Abstract: Telehealth use has increased in the setting of the COVID-19 pandemic. However, there are disparities in telehealth use based on age, income, race/ethnicity, low health, digital literacy, and limited English proficiency. There are multilevel barriers to telehealth use at the patient, health systems, telehealth portal, and policy levels. To ensure equity in telehealth services and to leverage these services to maximize the reach of health care services, concerted efforts are needed to design telehealth tools and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 23 publications
1
46
0
1
Order By: Relevance
“…The coronavirus disease 2019 (COVID-19) pandemic highlighted both the continued impact of long-standing systemic oppression on disparate health outcomes as well as the growing importance of digital healthcare. Several studies found significant differences in successful telehealth use in disparity populations [6][7][8] . Access to digital health is becoming an increasingly important determinant of health.…”
Section: Introductionmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID-19) pandemic highlighted both the continued impact of long-standing systemic oppression on disparate health outcomes as well as the growing importance of digital healthcare. Several studies found significant differences in successful telehealth use in disparity populations [6][7][8] . Access to digital health is becoming an increasingly important determinant of health.…”
Section: Introductionmentioning
confidence: 99%
“…A potential barrier with virtual education is equitable access, for example, in older demographics who are less likely to have access to digital health tools [11] . In this study however, most patients were eligible to participate and only a small proportion perceived or experienced technology-related issues and this barrier may not be as significant as previously thought [11] , [12] . Providing options for patients and considering individual preferences, including in-person or tele-education, would ensure equitable access and patient-centered care.…”
Section: Discussionmentioning
confidence: 67%
“…COVID-19 required us to investigate new and additional methods of service provision (Cacciante et al, 2021 ; Dixit et al, 2021 ). Our service package included face-to-face intervention, telehealth (asynchronous, synchronous and remote monitoring) or a hybrid model of incorporating the two.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Barriers include internal factors such as the lack of awareness and scepticism about change, technical readiness and external challenges such as costs, limited technical resources, data privacy issues and unclear liability of rehabilitation providers (Camden & Silva, 2021 ). Furthermore, Dixit et al ( 2021 ) identified limited access to telehealth in patients with low income, limited English proficiency, low health, computer literacy and those accessing public healthcare. To understand our patients’ needs and preferences, we conducted a telehealth access questionnaire.…”
Section: Findings and Discussionmentioning
confidence: 99%